Influence of drip lateral placement depth and fertigation level on germination, yield and water-use efficiency of cucumber (Cucumis sativus) - MALI, SANTOSH S; SINGH, RANVIR; SINGH, A K; MEENA, MUKESH (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted from February to June for three years (2009-2011) to evaluate the response of cucumber (Cucumis sativus L.) under 0 (surface) (D00), 5(D05), 10 (D10) and 15 (D15) cm depth of lateral placement and four levels of fertilizer application with NPK in the ratio of 50:30:30, 100:60:60, 120:90:90 and 150:120:120 kg/ha (F1, F2, F3 and F4). Uniformity of water application through subsurface drip irrigation (SDI) system was assessed every year. Soil moisture content in root zone, germination percentage, vine length and yield per plot were recorded and irrigation water use efficiency (IWUE) was estimated.It was observed that soil moisture content was higher and moisture profile was more uniform under SDI. Shallower depths of lateral, D00 and D05, resulted in higher seed germination percentage (92.8 and 90.2 %). Increased moisture and nutrient availability under D10 and D15 resulted in higher vine length (2.49 and 2.36m). During 2011, treatments D10 and D15 recorded highest mean yields of 31.7 and 32.9 t/ha, respectively. Fertigation level F3 recorded consistently higher mean yields for three consecutive cropping seasons yielding higher mean IWUE under D10 (0.49 to 0.81 t/ha/cm) and D15 (0.50 to 0.85 t/ha/cm).The results showed that SDI maintained uniform moisture in soil profile, minimized the evaporative loss and consequently increased IWUE. The SDI system with lateral placement depth of 10 cm and fertigation level F3 is recommended as an optimum practice for better yields and increased IWUE of cucumber cultivation.